2019
DOI: 10.1021/acs.jpcc.9b03769
|View full text |Cite
|
Sign up to set email alerts
|

Magnetically Induced Current Densities in Toroidal Carbon Nanotubes

Abstract: Molecular structures of toroidal carbon nanotubes (TCNTs) have been constructed and optimized at the density functional theory (DFT) level. The TCNT structures have been constrained by using point groups with high symmetry. TCNTs consisting of only hexagons (polyhex) with armchair, chiral, and zigzag structures as well as TCNTs with pentagons and heptagons have been studied. The employed method for constructing general polyhex TCNTs is discussed. Magnetically induced current densities have been calculated usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 23 publications
(30 citation statements)
references
References 109 publications
(201 reference statements)
1
27
0
Order By: Relevance
“…In the previous GIMIC studies, we successfully used the M06-2X functional in calculations on aromatic and antiaromatic porphyrinoids. 53 55 However, generally, the M06-2X functional exaggerates the diatropic contribution to the ring current, 55 , 56 which we actually also observe for C 60 –C 100 . The strength of the ring current gradually increases from 0.7 nA T –1 for C 44 to 2.4 nA T –1 for C 100 ( Figure 3 ).…”
Section: Resultssupporting
confidence: 68%
“…In the previous GIMIC studies, we successfully used the M06-2X functional in calculations on aromatic and antiaromatic porphyrinoids. 53 55 However, generally, the M06-2X functional exaggerates the diatropic contribution to the ring current, 55 , 56 which we actually also observe for C 60 –C 100 . The strength of the ring current gradually increases from 0.7 nA T –1 for C 44 to 2.4 nA T –1 for C 100 ( Figure 3 ).…”
Section: Resultssupporting
confidence: 68%
“…The ringcurrent strengths were calculated at the B3LYP level and the TPSS for comparison with results obtained in previous studies. 72 The inner and outer J ind fluxes have the same tropicity, when the external magnetic field is oriented along the torus symmetry axis. The inner J ind flux is though somewhat weaker than that outside the surface.…”
Section: Toroidal Nanotube C2016mentioning
confidence: 98%
“…16,86 When the external magnetic field is perpendicular to the CNT, the current density is diatropic inside and outside. Recently, Reiter et al 72 calculated the magnetically induced current densities of a family of toroidal carbon nanotubes (TCNT) using the GIMIC method. When the external field is applied along the torus symmetry axis, they found that TCNTs with HOMO-LUMO gaps larger than 0.2 eV generally sustain weak global ring currents and that the ring-current strength increases with increasing TCNT size.…”
Section: Toroidal Nanotube C2016mentioning
confidence: 99%
See 1 more Smart Citation
“…47 Calculations of the magnetic-field-induced current densities in organic molecules have been widely used to characterize ring currents 48 and aromaticity in large organic systems 32,49 including toroidal carbon nanotubes. 50 The magnetizability χ can also be defined as the secondorder derivative of the total energy E of the system with regard to B…”
Section: Theory and Calculation Of Diamagnetismmentioning
confidence: 99%